2018
DOI: 10.1186/s12889-018-5568-5
|View full text |Cite
|
Sign up to set email alerts
|

Maternal anemia is a potential risk factor for anemia in children aged 6–59 months in Southern Africa: a multilevel analysis

Abstract: BackgroundThe effect of maternal anemia on childhood hemoglobin status has received little attention. Thus, we examined the potential association between maternal anemia and childhood anemia (aged 6–59 months) from selected Southern Africa countries.MethodsA cross-sectional study using nationally representative samples of children aged 6–59 months from the 2010 Malawi, 2011 Mozambique, 2013 Namibia, and 2010–11 Zimbabwe demographic and health surveys (DHS) was conducted. Generalized linear mixed models (GLMMs)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

27
60
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(97 citation statements)
references
References 46 publications
27
60
1
1
Order By: Relevance
“…The current study found that there is a higher odds of anemia among women in the anemia cluster (identi ed by SaTScan) than outside of the cluster. This in line was the ndings of other studies (38,39). The possible explanation is that women with anemia and anemic children live in a similar socioeconomic, cultural and health related environment (37,40).…”
Section: Discussionsupporting
confidence: 90%
“…The current study found that there is a higher odds of anemia among women in the anemia cluster (identi ed by SaTScan) than outside of the cluster. This in line was the ndings of other studies (38,39). The possible explanation is that women with anemia and anemic children live in a similar socioeconomic, cultural and health related environment (37,40).…”
Section: Discussionsupporting
confidence: 90%
“…Moreover, the usual definition of PPH (blood loss ≥500 mL during vaginal delivery and ≥1000 mL during cesarean section) may not be clinically relevant in sub‐Saharan Africa, where small amounts of blood loss may have detrimental outcomes in patients with preexisting severe (hemoglobin <7 g/d) or moderate anemia (hemoglobin 7‐9.9 g/d). Although never formally studied, this is important to note, since the prevalence of maternal anemia approaches 80% in some countries, compared to approximately 5% in the United States . Additionally, there is clinical evidence that anemia can increase the risk of surgical bleeding and PPH …”
Section: Introductionmentioning
confidence: 99%
“…Although never formally studied, this is important to note, since the prevalence of maternal anemia approaches 80% in some countries, compared to approximately 5% in the United States. [12][13][14][15] Additionally, there is clinical evidence that anemia can increase the risk of surgical bleeding and PPH. [16][17][18][19][20] In an effort to target interventions to prevent and treat PPH in Mozambique, we sought to define the rate of PPH and identify risk factors that contribute to PPH and mortality in Maputo Central Hospital, the largest university hospital in Mozambique.…”
Section: Introductionmentioning
confidence: 99%
“…Maternal obesity increases the risk of various adverse pregnancy outcomes [3] and can affect offspring health [4,5]. Previous studies showed that maternal obesity had been linked to maternal anemia [6,7] and iron deficiency [8] that can predispose offspring to anemia [9,10]; maternal obesity could reduce the iron store of newborn [11][12][13][14] that likely leads to anemia in later life [15]. However, direct assessment of the association between maternal obesity and offspring anemia is lacking.…”
Section: Introductionmentioning
confidence: 99%